PENGARUH GENDER, KOMPLEKSITAS TUGAS DAN PRESEPSI ETIS TERHADAP PERTIMBANGAN AUDIT (Studi Pada Kantor Akutan publik di Wilayah Sumatera) - Rahayu, Listia Rini; -, Kamaliah; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed at investigating empirically the effect of gender, task complexity, and ethical perceptionon audit judgment. This study was a quantitative research that used primary data collected by questionnaire. The population consisted of auditors who worked with Sumatera KAP Representative, while the sampling technique used was purposive sampling with the criteria of auditors as follows. They have worked for more than one year and have audited for at least 10 times. The sample used in this study were 62 respondents senior auditors, junior auditor, suvervisor and partners (KAP) in Sumatra. Management and analysis of data using multiple linear regression analysis with SPSS version 20 (Statistical Product and Service Solution). Hypothesis testing results indicate that gender effectiveness, the complexity of the task and perception positive effect on audit judgment. The coefficient of determination in this study was 62.1% against the judgment of the audit, while the remaining 37.9% is influenced by other variablesKeywords: gender, task, ethical and audit judgment